Development and Validation of an RPA Assay for Detecting Xanthomonas citri subsp. citri A, A*, and Aw and X. fuscans subsp. aurantifolii B and C - Raquel S. Hill; Archana Pal; Megan M. Dewdney; Liliana Cano; Carrie Lapaire Harmon (PhytoFrontiers, 2025)
Citrus canker, caused by Xanthomonas citri subsp. citri (Xcc) and X. fuscans subsp. aurantifolii (Xfa), is a destructive disease of citrus. It is sparsely distributed in the Caribbean, and effective biosecurity measures, including accurate pathogen detection systems, are essential to prevent further spread. Current in-field screening methods rely on visual symptom identification and serological tools such as Agdia's X. axonopodis subsp. citri (Xac) ImmunoStrips (Elkhart, IN, U.S.A.). However, they failed to detect the Aw and C pathotypes in this study. Nucleic acid amplification is the gold standard for confirming detection but is resource-intensive and less accessible in Caribbean plant diagnostic laboratories and regulatory services. To address this, a rapid recombinase polymerase amplification (RPA) assay was developed using a portable fluorometer and primers designed to detect all canker-causing pathotypes. The RPA assay accurately detected all five citrus canker pathotypes and was selective against X. euvesicatoria pv. citrumelonis, the fastidious citrus greening bacteria ‘Candidatus Liberibacter asiaticus’, and the xylem-limited bacterial pathogen Xylella fastidiosa. However, X. perforans, X. citri pv. glycines, and X. citri pv. phaseoli, pathogens unrelated to citrus and unlikely to be present in citrus, were detected. Real-time detection was completed in 25 min with high sensitivity levels of 0.001 pg/µl (Xcc A), 0.1 pg/µl (Xfa B), and 1 pg/µl (Xfa C) of DNA. This RPA assay offers a robust, in-field detection method, combining molecular sensitivity and specificity with the field-friendly simplicity of crude extraction and single-tube reactions. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.